Tanah Pertanian dalam Perspektif Hukum Islam - Jefri Putri Nugraha (Transformasi : Jurnal Studi Agama Islam, 2017)
One of the problems in agriculture in Indonesia is the problem of agricultural land. There are five land issues in Indonesia, namely: (1) wide narrow farmland ownership; (2) decreased land productivity; (3) the occurrence of land conversion that grew larger for non-agricultural purposes; (4) not yet optimal implementation of commodity mapping related to agro ecosystem; And (5) there is still a lot of sleeping land. The solution of those problems has indeed been initiated and some of them have been implemented. But the solution seems to be a purely technical solution, without incorporating Sharia as a law capable of dealing with such problems. This paper aims to explain the Islamic sharia laws related to agricultural land and agricultural policy in Islam.